Visceral malperfusion syndrome masks in acute type B aortic dissection - N. Yashchuk; I. Ditkivskyy; B. Cherpak; V. Kravchenko; V. V. Lazoryshynetz (Ukrainian Journal of Cardiovascular Surgery, 2019)
Acute aortic dissection (AAD) is a life-threatening condition associated with high morbidity and mortality rates, and it remains a challenge to diagnose and treat. Visceral malperfusion syndrome affects almost 21% of the patients with acute type B aortic dissection. Moreover, according to the IRAD (International Registry of Aortic Dissection) data, it is an independent risk factor for hospital mortality and accounts for 30.8%. A wide variability of symptoms causes delay in diagnosing in 28% of the patients with abdominal pain thus explaining a high mortality rate.Case description. This manuscript presents a case of successful treatment of dynamic visceral malperfusion in a man pre-senting with the symptoms of acute pancreatitis and a two-week delay in diagnosing. The patient had an entry tear covered with a thoracic endovascular stent graft (TEVAR) following visceral flow restoration. Due to the persistent abdominal pain despite successful repair, the patient underwent diagnostic laparoscopy in order to assess the bowel viability. Normal bowel passage was restored one month after the TEVAR procedure.Discussion. Visceral ischemia is a life-threatening complication of acute type B aortic dissection. Presentation of visceral ischemia can be challenging, which may lead to crucial delays in diagnosis and treatment. The mechanism of compromised branch vessels can be both static and dynamic. In cases of suspicion of ABAD with visceral ischemia, urgent additional imaging, preferably CTA should follow. After CTA however, doubts may remain regarding visceral malperfusion, as no in-volvement of visceral vessels is seen in 20% of these patients. These patients usually have dynamic obstruction by prolapse of the dissection flap into the vessel ostium. Urgent restoration of the visceral organ perfusion should be the first step of management. The management of dynamic obstruction involves different approaches: from TEVAR with an entry tear to the false lumen coverage by TEVAR to intimal flap fenestration via the funnel technique. After successful restoration of vis-ceral perfusion, patients should be monitored closely, and the bowel should be examined when there is a doubt regarding its viability. Generally, bowel resection may be needed in 14 to 53% of the patients presenting with acute mesenterial ischemia.The International Registry of Acute Aortic Dissection (IRAD) database recognizes malperfusion in 21% of the patients with Stanford type B aortic dissection. However, acute pancreatitis is not described as an ischemic complication of acute aortic dissection in the IRAD. As the precise aetiology of pancreatitis following aortic dissection continues to be elucidated, what remains is the diagnostic challenge of efficiently differentiating between the clinical manifestations of aortic dissection and other aetiologies of acute abdominal pain such as acute cardiac ischemia, pancreatitis, or intestinal obstruction. Acute pancreatitis presenting as acute aortic dissection is a rare entity with less than ten well-documented cases reported so far. It is hypothesized that the pancreas can be susceptible to hypoperfusion as seen in cardiopulmonary bypass surgery. We present a case misdiagnosed as acute pancreatitis only based on the clinical symptoms and later correctly diagnosed as an aortic dis-section when the symptoms did not improve.Conclusion. Acute aortic dissection may be a mask of different diseases. In not explainable and not curable situations, CTA plays an important role in diagnosis and management of the disease.